Causes and Impact of Port Accident on Operational Performance of Nigerian Seaport at Tin Can Island, Lagos Nigeria - A. R. Okpara; O. J. Anyanwu; A. I. Dirisu; O. C. Okorefe (Journal of Applied Sciences and Environmental Management)
The objective of this paper is to identify the causes and impact of port/harbor accident on operational performance at Tin Can Island, Lagos, Nigeria using appropriate standard methods to obtain primary and secondary data from reliable sources by distributing 80 questionnaires. Data obtained show that the major causes of accident include; over capacity usage, failure to consider dangerous goods’ separation and coordination deficiency by management. The study's findings indicate that, based on the survey data that was collected and the testing of each listed hypotheses, all of the hypotheses were found to be significant, this relationship can be seen in the ANOVA table where the significance value of the F statistics is greater than 0.05 which means the variation explained by the model is due to chance. It was recommended that seaports should regulatory bodies and port operators should enforce safety regulations and provide adequate training and safety measures to prevent accidents and improve the safety and efficiency of port operations.